Comparison of clinical outcomes of sitagliptin+metformin combination and glimepiride in the management of uncomplicated type 2 diabetics - Tahashildar, Jarinabanu; Singh, Ravi Shekhar; Tahashildar, Jameela (International Journal of Basic & Clinical Pharmacology, 2018)
Background: To evaluate the comparison of clinical outcomes of sitagliptin +metformin and glimepiride in uncomplicated Type-2 diabetics. Methods: This one year (July 2016 to August 2017) prospective, open label, observational clinical cohort study was carried out on type-2 diabetics. In this study 299 Type-2 diabetics patients were enrolled and were randomly allocated to two groups viz Group A and Group B. Group A received sitaglitin+metformin (50+500) mg/day and Group B received glimepiride 1mg/day respectively. The follow up started after 10 days of stabilization of the patient and data recorded on 10th day was considered Zero month data and follow up continued up to Six month in each group. Comparison of FPG, PPG and HbA1c was evaluated between zero and six months within group and at six month between groups. Adverse events were recorded and summarized by treatment group. Results: At the end of six months follow up the patients of Group A who received sitaglitin+metformin (50+500) mg/day had greater reduction in FPG, PPG and HbA1c (all P<0.001) was recorded when compared between zero and six month within group. A significant reduction in FPG, PPG and HbA1c (all P<0.01) also recorded in Group B who received glimepiride 1mg/day when compared between zero and six months within group. A statically significant difference (all P<0.05) was recorded at six months between group. The adverse events like hypoglycemic episodes, gastrointestinal adverse events etc were greater in Group B than Group A. Changes in weight also noted in both Groups. Weight loss in Group A and weight gain in Group B was recorded. Conclusions: The present study suggests that a significant difference may be existing in the clinical outcome interm of glycemia control and adverse events between sitagliptin+metformin combination and glimepiride in type-2 diabetic patients.